Importance of Innovation Resources for Market Orientation – Financial Performance Link: Mediating Role of Proactive Market Orientation - Milfelner, Borut; Dlačić, Jasmina; Snoj Boris; Selinšek, Aleksandra (Naše gospodarstvo/Our economy, 2019)
The purpose of this paper is to explore the relationship between market orientation, innovation resources and companies’ financial performance. Focus is put on the mediator role of proactive market orientation (PMO) in the relationship between reactive market orientation (RMO), innovation resources and financial performance in the context of Central and Eastern European (CEE) countries. Research builds on reliable scales. Four hundred and fifteen usable questionnaires were collected from companies in Slovenia with more than 20 employees. The results show a strong and positive relationship between RMO and PMO. The impact of RMO on innovativeness as an element of organisational culture is both positive and stronger than the impact of PMO. PMO proved to have a significant positive influence on the capacity to innovate. While innovativeness alone does not directly influence financial performance, the results do confirm the positive impact of an organisational capacity to innovate on financial performance. The finding of our paper is that when PMO was included as a mediator between RMO and the capacity to innovate, the result was that this indirect impact proved to be one of the strongest in the model. Also, it proves that in CEE countries, it is important to stress the influence of market and market orientation in building innovation resources and consequently financial performance. The limitation of the current study is that we considered the relationship only among few marketing resources and organisational performance. In future research, additional measures of market performance may be introduced as mediators between innovation resources and financial performance.